Hubungan morfologi telur dengan bobot telur dan bobot DOC dengan bobot badan ayam Kampung F1 - Depison Depison; Redo Prawira; Gushariyanto Gushariyanto; Silvia Erina (Jurnal Ilmu Peternakan Terapan, 2021)
This study aims to determine the relationship between egg morphology and egg weight and DOC weight with body weight of Kampung F1 chickens. The research material was 174 free-range chickens from hatching 315 eggs. The method used: experimental method. Data collected: egg size, egg weight, body weight, body weight gain, and body size. Data on egg size, egg weight, body weight, body weight gain and body size were analyzed using a t-test. The relationship between variables was analyzed regression and correlation analysis. Characteristics of body size and shape were analyzed principal component analysis. The results showed that egg size, egg weight, body weight, body weight gain and body size of male Kampung chickens were different (P <0.05) higher than females. Egg size affects egg weight, and DOC weight affects body weight at 4, 8, and 12 weeks of age. Egg size was positively correlated with male and female egg weights. DOC weight was positively correlated with body weight of Kampung chickens aged 4, 8, and 12 weeks. The closest correlation between egg size and egg weight was egg circumference (0.913), and DOC weight with body weight was weight at 4 weeks of age (0.936). In conclusion, the relationship between egg size and egg weight,  DOC weight and body weight were linear and  had appositive values.